A primer on propensity score matching estimators (2006)
Nonparametric matching estimators are frequently applied in evaluation studies. The general idea of the methodology is to determine the impact of treatment on the treated using information from treated and from similar non-treated observations to build a counterfactual of no treatment. I discuss the methodology for both the binary treatment case as well as for the multiple treatment case.